Exogenous nitrogen input skews estimates of microbial nitrogen use efficiency by ecoenzymatic stoichiometry - Sun, Lifei; Moorhead, Daryl L.; Cui, Yongxing; Wanek, Wolfgang; Li, Shuailin; Wang, Chao (Ecological processes, 2023)
Background Ecoenzymatic stoichiometry models (EEST) are often used to evaluate microbial nutrient use efficiency, but the validity of these models under exogenous nitrogen (N) input has never been clarified. Here, we investigated the effects of long-term N addition (as urea) on microbial N use efficiency (NUE), compared EEST and 18 O-labeling methods for determining NUE, and evaluated EEST’s theoretical assumption that the ratios of standard ecoenzymatic activities balance resource availability with microbial demand. Results We found that NUE estimated by EEST ranged from 0.94 to 0.98. In contrast, estimates of NUE by the 18 O-labeling method ranged from 0.07 to 0.30. The large differences in NUE values estimated by the two methods may be because the sum of β-N-acetylglucosaminidase and leucine aminopeptidase activities in the EEST model was not limited to microbial N acquisition under exogenous N inputs, resulting in an overestimation of microbial NUE by EEST. In addition, the acquisition of carbon by N-acquiring enzymes also likely interferes with the evaluation of NUE by EEST. Conclusions Our results demonstrate that caution must be exercised when using EEST to evaluate NUE under exogenous N inputs that may skew standard enzyme assays.